Imaginary histories: ancient Egypt in the writings of Marguerite Yourcenar and Philippe Derchain - Parkinson, R (Helmut Buske Verlag, 2019)
This published version of a memorial lecture in honour of Philippe Derchain discusses Marguerite Yourcenar’s treatment of Ancient Egypt in her writings, and compares Derchain’s literary writings in order to suggest similarities and differences in their handling of Ancient Egyptian sources, especially the Monte Pincio obelisk. An examination of Yourcenar’s sources shows how she, as a ‘queer’ writer, prioritised Hadrien’s emotional experiences over factual accuracy and official heteronormative expectations. Both authors championed a selfreflexive use of imagination in dealing with ancient sources, and a concern for the ‘inner life’ of ancient people.